ANTIBACTERIAL EFFECTIVITY OF FLAVONOID FRACTION OF RAMANIA LEAF EXTRACT (Bouea macrophylla Griffith) AGAINST Porphyromonas gingivalis - Lailatul Qomariyah; Fransiska Uli Arta Panjaitan; Rosihan Adhani (Dentino : Jurnal Kedokteran Gigi, 2021)
Background: Chronic periodontitis is a periodontal disease with 80% of all cases of periodontitis. The major causes are the accumulation of plaque and bacteria. The dominant bacteria in chronic periodontitis is Porphyromonas gingivalis. Treatment of chronic periodontitis can be done by scaling and root planing and supporting therapy by using mouthwash such as Chlorhexidine gluconate 0.2% which is the gold standard in the treatment of periodontal disease. Chlorhexidine gluconate 0.2% has disadvantages so that nowadays research on herbal plants is being done to find alternative medicines that are more effective. Ramania (Bouea machropylla Griffith) leaf contains flavonoids that have antibacterial properties. Objective: To analyze the antibacterial effectivity of the flavonoid fraction of Ramania leaf extract against Porphyromonas gingivalis that causes chronic periodontitis. Method: True experimental study and post-test with control group design consisting of 5 treatment groups, namely flavonoid fraction of ramania leaf extract with concentrations of 0.1%, 0.3%, and 0.5%, chlorhexidine gluconate 0.2% as a control positive and aquadest as a negative control. Each group was repeated 6 times. Antibacterial tests using the dilution method with inhibitory rates calculated using a UV-Vis spectrophotometer and killing rates were calculated using a Colony Counter. Results: The average difference in absorbance values obtained inhibitory rates at concentrations of 0.1%, 0.3%, and 0.5%. One Way Anova Test showed a significance value of 0,000 (p < 0.05). The average number of colonies after 24 hours incubation showed the results of a kill rates in the concentration group of 0.3%, 0.5%, and positive control. The Kruskal Wallis test showed a significance value of 0,000 (p < 0.05). Conclusion: The minimum inhibitory concentration (MIC) was obtained at a concentration of 0.1% and the minimum bactericidal concentration (MBC) was obtained at 0.3% concentration. Keywords: Flavonoid Fraction, MIC, MBC, Porphyromonas Gingivalis, Ramania Leaf Extract.